2008
DOI: 10.1002/adfm.200800805
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Modeling of Ion Conduction of Nanosized CaF2/BaF2 Multilayer Heterostructures

Abstract: Molecular beam epitaxy‐grown CaF2/BaF2 heterolayers are a demonstration of the potential of nanoionics. It has been shown that ion conductivities both parallel and perpendicular to the interfaces increase with decrease in interfacial spacing. This size effect was attributed to the thermodynamically necessary redistribution of the mobile fluoride ions (N. Sata, K. Eberl, K. Eberman, J. Maier, Nature 2000, 408, 946; X. X. Guo, I. Matei, J.‐S. Lee, J. Maier, Appl. Phys. Lett. 2007, 91, 103102). On this basis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…This effect was related to the variation of the charge carriers density, or their mobilities, indicating the importance of the interfaces in enhancing charge transport phenomena beyond trivial size effects of increasing surface-tovolume ratio in nanocrystalline material. Epitaxial heterostructures prepared by sequential deposition of CaF 2 /BaF 2 have also shown enhancement of the F -ionic conductivity along the interfaces, by several orders of magnitude, upon reducing the thickness to a few nanometers [7,8]. This effect was attributed to the variation of the density of majority charge carriers in the space charge region generated at the interfaces between both materials.…”
Section: Introductionmentioning
confidence: 85%
“…This effect was related to the variation of the charge carriers density, or their mobilities, indicating the importance of the interfaces in enhancing charge transport phenomena beyond trivial size effects of increasing surface-tovolume ratio in nanocrystalline material. Epitaxial heterostructures prepared by sequential deposition of CaF 2 /BaF 2 have also shown enhancement of the F -ionic conductivity along the interfaces, by several orders of magnitude, upon reducing the thickness to a few nanometers [7,8]. This effect was attributed to the variation of the density of majority charge carriers in the space charge region generated at the interfaces between both materials.…”
Section: Introductionmentioning
confidence: 85%
“…[2][3][4][5] These efforts have been comple-mented by a series of modeling studies that have resulted in a very detailed picture of nanoscale heterolayer systems. [6,7] An alternative approach to such interface-dominated materials has involved studying the ionic conductivity of clusterassembled nanocrystalline CaF 2 and BaF 2 homo-and heterosystems that were prepared by inert-gas condensation or by high-energy ball-milling. [8][9][10][11][12][13] In such systems, the introduction of interfacial defects can be understood in terms of a heterogeneous Frenkel reaction [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ionic conductivity of nanoscale materials can be further enhanced by developing multilayer thin films with nanoscale interfaces [202][203][204]. It has been observed that, nanoscale hetero-structures of CaF 2 and BaF 2 exhibit significantly higher ionic conductivity along the interfacial direction at moderate temperatures due to the redistribution of mobile fluoride ions in the overlapped space-charge regions of CaF 2 and BaF 2 [18,205,206]. These results paved the way to develop multilayer thin film electrolytes to enhance the oxygen ionic conductivity by introducing hetero-structured interfaces [59,61,[207][208][209][210][211][212][213][214].…”
Section: Multilayer Hetero-structured Thin Film Electrolytesmentioning
confidence: 98%